Proton pump inhibitors and dementia : Physiopathological mechanisms and clinical consequences (2018)
Alzheimer's disease (AD) is the most common type of dementia, mainly encompassing cognitive decline in subjects aged =65 years. Further, AD is characterized by selective synaptic and neuronal degeneration, vascular dysfunction, and two histopathological features: extracellular amyloid plaques composed of amyloid beta peptide (Aß) and neurofibrillary tangles formed by hyperphosphorylated tau protein. Dementia and AD are chronic neurodegenerative conditions with a complex physiopathology involving both genetic and environmental factors. Recent clinical studies have shown that proton pump inhibitors (PPIs) are associated with risk of dementia, including AD. However, a recent case-control study reported decreased risk of dementia. PPIs are a widely indicated class of drugs for gastric acid-related disorders, although most older adult users are not treated for the correct indication. Although neurological side effects secondary to PPIs are rare, several preclinical reports indicate that PPIs might increase Aß levels, interact with tau protein, and affect the neuronal microenvironment through several mechanisms. Considering the controversy between PPI use and dementia risk, as well as both cognitive and neuroprotective effects, the aim of this review is to examine the relationship between PPI use and brain effects from a neurobiological and clinical perspective. © 2018 Gloria Ortiz-Guerrero et al.